A Biodegradable Copolyester, Poly(butylene succinate-co-ε-caprolactone), as a High Efficiency Matrix Former for Controlled Release of Drugs - Eduardo Galdón; Mónica Millán-Jiménez; Gloria Mora-Castaño; Antxon Martínez de Ilarduya; Isidoro Caraballo (Pharmaceutics, 2021)
A biodegradable copolyester, poly(butylene succinate-co-ε-caprolactone) (PBS_CL), was used for first time as an excipient for pharmaceutical dosage forms using direct compression and hot processing techniques (ultrasound-assisted compression (USAC) and hot melt extrusion (HME)). Robust binary systems were achieved with hot processing techniques, allowing a controlled release of the drug. With only 12% v/v of PBS_CL, controlled release forms were obtained using USAC whereas in HME over 34% v/v of excipient is necessary. Amounts over 23% v/v allowed a long-extended release for more than 72 h following diffusional kinetic. Thanks to the high melting point of theophylline and the physicochemical properties of PBS_CL selected and synthesized, the structure of the excipient inside the USAC tablets and HME filaments corresponds to a continuum medium. A percolation threshold around 23% v/v was estimated, which agrees with a continuum percolation model. The polymer shows a high excipient efficiency value using HME and USAC. A nanostructured matrix with wall thicknesses lower than 0.1 µm was obtained. This leads to a very effective coating of the drug particles by the excipient, providing a slow and reproducible release. The present study therefore supports the use of PBS_CL, for the preparation of controlled release dosage forms using hot processing techniques.